PERSEPSI PENGRAJIN TERHADAP PENGEMBANGAN INDUSTRI RUMAH PANGGUNG DI DESA MOKOBANG KECAMATAN MODOINDING - Githa Claudia Waworuntu; Charles Reijaaldo Ngangi; Caroline Besty Diana Pakasi (Sam Ratulangi University, 2019)
This study aims to examine how the craftsman's perception of the development of the stilt house industry in the village of Mokobang, Modoinding District, South Minahasa Regency. The research lasted for two months starting from February to April 2017 in Mokobang Village, Modoinding Sub-district, Minahasa Regency. The data used are primary data and secondary data. Primary data is data obtained from direct interviews with 50 respondents of stage home industry craftsmen who were chosen purposively. Interviews were conducted with the help of a questionnaire prepared previously and using a Likert Scale. Secondary data were obtained from the Mokobang Village Office and the internet. From the internet through Google searching to get articles from various journals related to research topics about the perception of craftsmen on the development of the stage home industry. The data obtained were analyzed using descriptive analysis and presented in a table. The results showed that the public perception of the development of the wooden stilt house industry in Mokobang Village, Modoinding Sub-district, South Minahasa Regency was classified in the good category, which was based on indicators of perception of the availability of wood raw materials, labor and knowledge about wood quality.*eprm*